Parenting coordination – outcome measurement and prediction: Implications for research and practice. (11th December 2022) - Or Sharvit, Zohar; Sorek, Yoa; Honigman, Idit
Abstract: This paper presents a formative evaluation study of the parenting coordination pilot program launched in Israel in 2016 at the initiative of the Ministry of Welfare and Social Affairs (At the time the program was launched, the Ministry of Labor, Social Affairs and Social Services) and JDC‐Ashalim. Data was collected on 131 participating families (262 parents) through self‐administered questionnaires filled out by the parents prior to the parenting coordination process ( N  = 204), telephone interviews with the parents following the process ( N  = 142), and reports by the parenting coordinators (PCs), submitted online at the conclusion of the process with each participating family ( N  = 131). Based on the logic model developed as a blueprint for the pilot program, the characteristics and needs of parents in high conflict were identified and desired outcome indicators were accordingly specified; quantitative and qualitative research tools were developed for the study, and the efficacy and outcomes of the parenting coordination pilot program were evaluated. Overall, the findings indicate a significant improvement in the desired outcome indicators. The implications of the findings for research and practice are discussed in the conclusion. Key points for the family court community: Based on a large sample of families in high conflict who participated in the parenting coordination pilot program and matched PCs, this pioneering study offers fresh insights on the efficacy and outcomes of parenting coordination—so far addressed by rather limited research. Overall, parents in high conflict experienced a significant improvement in the desired outcome indicators following participation in the parenting coordination pilot program although most of them withdrew from the program ahead of schedule. Higher success rates were found among parents who refrained from reverting to litigation over their children in the course of the parenting coordination process. Lower intensity levels of the parental conflict prior to parenting coordination (along a continuum of high‐intensity parental conflict: from moderate/high through intense to extreme), longer parenting coordination time ranges, including more sessions, up to the specified limit, and completion of the process as scheduled, without suspension due to reapplication to the court, were found to be successful outcome predictors. A significant reduction in both inter‐parental and child‐directed violence was found in this study, indicating the efficacy of the approach adopted and the intervention tools used in the pilot program in maintaining and safeguarding the well‐being of the children entangled in the parental conflict. An improvement was also found in the various aspects of parents' ability to shield their children from the parental conflict, which was the overarching goal of the program.